A Review of Hexapod Robot Research: From Structural Design to Intelligent Control - Gu , Shuowen (International Journal of Mechanical and Electrical Engineering, 2026)
Hexapod robots, their exceptional static stability, redundant limb structures, and strong terrain adaptability, demonstrate broad application prospects in fields such as interstellar exploration, disaster rescue, military reconnaissance, and complex environment operations. Based on a systematic review of multiple high-quality academic papers published in recent years, this paper provides an in-depth review of the current state of hexapod robot technology from key dimensions, including mechanical structure design and optimization, kinematics and dynamics modeling, gait planning and motion control, environmental perception and autonomous decision-making, and adaptability under special operating conditions. The analysis indicates that current research is shifting from traditional single-structure, regular gait, and model-dependent control toward lightweight/reconfigurable structures, adaptive gaits for complex terrains, and intelligent control based on deep reinforcement learning. In the future, integrating advanced sensing technologies and achieving higher autonomy and environmental robustness will be key breakthroughs in hexapod robot research.